Utilizing network pharmacology to explore potential mechanisms of YiSui NongJian formula in treating myelodysplastic syndrome. Issue 1 (1st January 2021) - Qin, Lerong; Chen, Haiyan; Ding, Xiaoqing; Guo, Ming; Lang, Haiyan; Liu, Junxia; Li, Ling; Liao, Jing; Liao, Junyao
ABSTRACT: The study aims to explore potential mechanisms of YiSui NongJian formula (YSNJF) in treating myelodysplastic syndromes (MDS) by network pharmacology-based strategy. Active compounds and corresponding potential therapeutic targets of YSNJF were harvested by utilizing the database of TCMSP (Traditional Chinese Medicine Systems Pharmacology) and BATMAN-TCM (Bioinformatics Analysis Tool for Molecular mechanism of Traditional Chinese Medicine). MDS targets were adopted from GeneCard, KEGG (Kyoto Encyclopedia of Genes and Genomes), TTD (Therapeutic Target Database), DrugBank, and DisGeNet. Then a network of YSNJF- compounds-target-MDS network was harvested. The protein–protein interaction (PPI) network was then generated by the Sting database and subjected to Cytoscape software to harvest major and core targets network by topological analysis. Genes from the core targets network were further subjected to Gene Ontology (GO) and KEGG enrichment analysis to figure out potential targeting pathways. Finally, a compounds-targets-pathways network was generated by Cytoscape. A total of 210 active compounds and 768 corresponding potential therapeutic targets were harvested from ingredients of YSNJF. MDS was shown to have 772 potential treating targets with 98 intersected targets corresponding to 98 active compounds in YSNJF. Topological analysis revealed that 15 targets formed the core PPI network. Further, GO and KEGG enrichment analysis revealed that those core targets were mainly enriched on cell cycle- and immune-related pathways. The present study revealed that therapeutic effects of YSNJF on MDS might be achieved through regulating cell cycle- and immune-related pathways. Graphic abstract: uf0001